(untitled) (Educação em Revista, 2023)
Despite society’s adoption of mobile devices, we have yet to gain an understanding whether teachers perceive these artifacts as an innovation and on their potential for teacher development and instruction. This qualitative study looks into mobile application affordances in these contexts and what these affordances reveal regarding the adoption of innovation in Rogers’ (2003). The study relied on the participation of eleven teachers and the findings indicate that these teachers perceive the affordances of their mobile device for professional development. As for instruction, these teachers report that lack of school equipment and the need for a curriculum that includes the use of emergent technologies may be considered indicative of a low degree of compatibility, an attribute regarding social system’s values. The affordances reported by the teachers seem to indicate the need for a new value system if the adoption of mobile learning is to occur place in formal educational